Switch to mania after acute antidepressant treatment for bipolar depression: a systematic review and network meta-analysis of randomised controlled trialsResearch in context - Vincenzo Oliva; Michele De Prisco; Enrico La Spina; Sofia Paolucci; Giovanna Fico; Gerard Anmella; Diego Hidalgo-Mazzei; Andrea Murru; Maurizio Pompili; Michele Fornaro; Marco Solmi; Ayşegül Yildiz; et al. (EClinicalMedicine)
Summary: Background: The potential for antidepressants to induce a switch to mania remains a major concern in the treatment of bipolar depression, but the specific risk associated with different antidepressants remains unclear. This systematic review and network meta-analysis (NMA) assessed this risk by comparing individual antidepressants with each other and with a common placebo. Methods: In this systematic review and network meta-analysis, we searched ClinicalTrials.gov, CENTRAL, PsycINFO, PubMed, Scopus, and Web of Science from database inception up to Feb 19, 2025, with no language restrictions, for randomised controlled trials (RCTs) assessing acute antidepressant treatment in bipolar depression. The primary outcome was the rate of switch to mania after antidepressant treatment. A frequentist NMA estimated risk ratios (RRs) and 95% confidence intervals. Sensitivity analyses were performed based on treatment regimen (monotherapy or add-on), baseline severity, switch to mania definition, study setting, psychiatric comorbidity, treatment duration, non-pharmacological combinations, industry sponsorship, and risk of bias. Certainty of evidence was assessed using the CINeMA framework. The protocol was preregistered on the Open Science Framework. Findings: Of 2434 records screened, 13 RCTs (1362 patients; 818 [60.1%] female, 511 [37.5%] male, and 33 [2.4%] not disclosed) were included in the NMA. Although some evidence of increased risk of switching to mania was observed, no antidepressant was associated with a significantly higher risk of switch to mania compared to placebo. Venlafaxine showed the highest risk estimate among antidepressants, though not statistically significant RR (4.53 [95% CI 0.47–43.25]), and was the only compound with consistent signals of increased switch in individual studies. The evidence base was larger for add-on therapy, while fewer data were available for monotherapy. Sensitivity analyses confirmed the results. Heterogeneity was low. Overall confidence in the evidence was rated as low. Interpretation: Antidepressants remain a treatment option for acute bipolar depression, particularly as add-on therapy. Their use should be individualised, considering patient-specific profiles and other potential risks, in line with a precision psychiatry approach. Further studies are needed to clarify long-term safety. Funding: None.